Islamic Financial Technology dalam Kajian Filsafat Ilmu - Heni Hirawati; Mugi Harsono (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Islamic financial technology (fintech) has experienced rapid development but is still not comparable to conventional fintech developments. This study aims to examine the construct of Islamic fintech in the view of the philosophy of science from the aspects of ontology, epistemology, and axiology. Islamic fintech is an interesting research area and continues to grow in the field of management, especially financial management. The method used is a literature review, which discusses the meaning, history, theory, and benefits of Islamic fintech to get a more detailed picture of Islamic fintech from previous researchers. This research also identifies the antecedents and consequences of Islamic fintech. The antecedents of Islamic fintech consist of resources, risks, profits, and competition which are factors of the company, as well as literacy, attitude, and acceptance, which are factors of consumers, and regulations from policymakers. The consequence of Islamic fintech is a sustainable finance system.